Community and conservation in Wallacea: Making the case for the region, a methodological framework, and research trends - Micah R. Fisher; Bart Verheijen; Muhammad Alif K. Sahide (Forest and Society, 2020)
This introduction provides a review of articles published in the special section on community conservation in the Wallacea region. As editors to the special section, we worked with contributors over a series of workshops to reflexively identify challenges to conducting research on community and conservation in this important and often overlooked region. The challenges are attributable to the dynamism and remoteness of the region, as well as its peripheral position relative to the center of government in Indonesia. We begin this article by making the case for a concerted field of study for the Wallacea region. Next, we draw on empirical research and continued engagement from across Wallacea to propose a framework that helps make better sense of the often perplexing trends involving communities and conservation in the region. We call the framework ASLi, which addresses the key institutions that negotiate conservation and development, including Adat and adaptive local institutions and the State. We situate these institutions within the dimensions of Livelihoods and their relations with natural resources. In testing out the framework with research groups and practitioners from across the region, we found that each of the aspects of the framework are fundamental for better understanding and facilitating policy discussions involving communities and conservation. In the second part of the article we shift our attention to assessing the empirical contributions from the special section. The empirical examples include eight articles from across the provinces of Sulawesi, East Nusa Tenggara, Maluku, and North Maluku. The issues range from topics that include: illegal species trade; human environment relations around charismatic species (e.g. komodo-community relations); watersheds, lakes, and landscapes; ecotourism; policy analysis; conservation management and planning; and, community participation and collaborative governance. There is much that remains misunderstood and misinterpreted about the Wallacea region. This initial set of consolidated and rich empirical material, combined with an organizing framework for continuing to study these issues, charts new horizons for future research.